Strong k-Barrier Coverage for One-Way Intruders Detection in Wireless Sensor Networks. (7th June 2016) - Luo, Junhai; Zou, Shihua
Abstract : Intruders detection is one of the very important applications in Wireless Sensor Networks (WSNs). Sometimes detecting intruders is not sufficient; distinguishing whether an intruder is legal or illegal is necessary. Since k -barrier coverage is widely used in detecting intruders, a barrier construction algorithm is needed, which can not only detect an intruder but also judge an illegal intruder. An intruder is defined as illegal if and only if it crosses straightly through the monitored region from the special side to another side. On the contrary, it is a legal intruder. To detect an intruder and distinguish whether the intruder is legal or illegal, a strong k -barrier coverage algorithm is proposed. The strong k -barrier coverage is a local barrier constructing algorithm and can detect any intruder crossing the k -barrier with a full probability. The strong k -barrier coverage detects all intruders penetrating the annular region for k times. What is more, the proposed strong k -barrier algorithm can provide a reliable judgement on whether an intruder is legal or illegal, and the constructed k -barrier coverage is different from the traditional one-way barrier coverage using binary barriers that are intersected but not overlapped. Some simulation tests show that the proposed algorithm can construct strong k -barrier coverage very well.